MON-723 Identification of Thyrotrope Signature Genes and Regulatory Elements - Daly, Alexandre (J Endocr Soc, 2020)
Recent genome wide association studies have begun to identify loci that are risk factors for sporadic pituitary adenomas, but the genes associated with these loci are unknown. In general, ~90% of GWAS hits are in noncoding regions, making it difficult to transition from genetic mapping to a biological understanding of risk factors. Recent studies that identify enhancer regions by undertaking large scale functional genomic annotation of non-coding elements like Encyclopedia of DNA Elements (ENCODE) have begun to yield a better understanding of some complex diseases. Dense molecular profiling maps of the transcriptome and epigenome have been generated for more than 250 cell lines and 150 tissues, but pituitary cell lines or tissues were not included. Epigenetic and gene expression data are emerging for somatotropes, gonadotropes and corticotropes, but there is very little available data on thyrotropes. We identified the transcription factors and epigenetic changes in chromatin that are associated with differentiation of POU1F1-expressing progenitors into thyrotropes using cell lines that represent an early, undifferentiated Pou1f1 lineage progenitor (GHF-T1) and a committed thyrotrope (TαT1). TαT1 is an excellent cell line for this purpose because it responds to TRH, retinoids, and secretes TSH in response to diurnal cues. We have also used genetic labeling and fluorescence activated cell sorting to purify thyrotropes from pituitaries of young mice and analyzed gene expression using single cell transcriptomics. We used the Assay for TransposaseAccessible Chromatin with sequencing (ATACseq) and Cleavage Under Target and Release Using Nuclease (CUT&RUN) to identify POU1F1 binding sites and histone marks associated with active enhancers, H3K27Ac and H3K4Me1, or inactive regions, H3K27Me3, in GHF-T1 and TαT1 cells. We integrated DNA accessibility, histone modification patterns, transcription factor binding and RNA expression data to identify regulatory elements and candidate transcriptional regulators. We identified POU1F1 binding sites that were unique to each cell line. For example, POU1F1 binds sites in and around Cga and Tshb only in TαT1 cells and Twist1 and Gli3 only in GHFT1 cells. POU1F1 binding sites are commonly associated with bZIP factor consensus binding sites in GHFT1 cells and Helix-Turn-Helix or basic Helix-Loop-Helix in TαT1 cells, suggesting classes of transcription factors that may recruit POU1F1 to unique sites. We validated enhancer function of novel elements we mapped near Tshb, Gata2, and Pitx1 by transfection in TαT1 cells. Finally, we confirmed that an enhancer element near Tshb can drive expression in thyrotropes of transgenic mice. These data extend the ENCODE analysis to an organ that is critical for growth and metabolism. This information could be valuable for understanding pituitary development and disease pathogenesis.